(untitled) (Eurasian Medical Research Periodical, 2022)
This article discusses about how a person ages, his or her body ages, the capacity of the cardiovascular system diminishes, hormones are disrupted, the function of all the sensitive analyzers is impaired, digestion of food becomes difficult, age-related changes in the joints and spine make movement difficult. In people over 70 years of age, gross metabolic disorders are observed in 70%, locomotor system disorders in 85%, reduced functionality of the brain (memory, thinking, depression, sleep disturbance) in over 90%. The sharp increase in vascular disease among the younger generation and the consequent development of vascular discirculatory encephalopathy should be taken into account.